Beyond facility-based births: Is Uganda delivering effective maternal and newborn care? An analysis of the 2022 demographic health survey and 2023 harmonized health facility assessment survey - Brian Turigye; Edgar Mugema Mulogo; Joseph Ngonzi; Peter M. Macharia; Miriam Acheng; Aliki Christou; Lenka Beňová (PLOS Global Public Health, 2025)
Maternal and newborn studies in Uganda have primarily focused on measuring contact coverage, such as the proportion of facility-based births. However, this is inadequate and may overestimate the benefits of services provided to women and newborns if the quality of care in the facilities is not considered. Effective coverage of care addresses this limitation and adjusts for the quality of services. This study assessed the effective coverage of maternal and newborn care for facility-based births in Uganda using the 2022 Uganda Demographic and Health Survey (DHS) and the 2023 Harmonized Health Facility Assessment (HHFA). The analysis included 5,618 women who had a live birth in the two years preceding the DHS, and 636 facilities providing childbirth care from the HHFA. Facility readiness was assessed using four domains: human resources, equipment, amenities, and drugs and supplies. Crude coverage was calculated as the percentage of facility births. Two measures of effective coverage were estimated: intervention coverage as a percentage of women who received all ten selected recommended interventions for their most recent birth, and readiness-adjusted coverage as a product of crude coverage and facility readiness using an ecological linking method by region. 85.9% of the women gave birth in a facility, but only 14.0% received all ten interventions. Readiness was highest in government hospitals (81.9%) and lowest in lower government health centers (46.4%). Only 47.8% of women gave birth in a ready facility. Readiness-adjusted coverage varied across regions, with the lowest in Kampala (40.9%) and the highest in the North-Eastern (61.4%). These Findings indicate a large gap between crude and effective coverage, disproportionately affecting regions and lower-level health centers, highlighting a need to enhance the capacity of lower-level health centers to deliver quality maternal and newborn care.
Keywords: Maternal and newborn studies; Facility-based births; Maternal and newborn care; Uganda